Morphometric Analyses of Phenotypic Plasticity in Habitat Use in Two Caspian Sea Mullets - Shima Bakhshalizadeh; Keyvan Abbasi; Adeleh Rostamzadeh Liafuie; Ali Bani; Anu Pavithran; Francesco Tiralongo (Journal of Marine Science and Engineering, 2022)
To understand the functional meaning of morphological traits in the exploitation of natural resources, it is necessary to develop a quantitative, meaningful scheme for understanding ecophenotypes; this will facilitate management and conservation, which are the most pressing challenges in vulnerable aquatic environments. In this context, the management of cryptic and very similar species is more challenging, because of the difficulty of distinguishing them and determining their frequency in sympatry, even though they do not necessarily have the same ecologies. As such, in order to understand how morphological similarities are associated with their ecology, thirteen morphometric characteristics related to body landmark-based geometric morphometries, sagittal otolith morphology, and shape were examined in mature Chelon auratus and Chelon saliens, which were collected from the coastal waters of the southwest Caspian Sea between October 2020 and April 2021. Univariate and multivariate analysis of variance were conducted to evaluate the potential morphological differences between the species. The analyses highlight the morphological differences between C. auratus and C. saliens, and identify potentially helpful traits for using body and otolith shape for the interspecific distinction of these very similar species of Caspian mullet, which can reflect functional similarity and are an important component of community ecology.